Effects of Multiple Injection Strategies on Heavy-Duty Diesel Energy Distributions and Emissions Under High Peak Combustion Pressures - Zhang, Zhao; Liu, Haifeng; Yue, Zongyu; Wu, Yangyi; Kong, Xiangen; Zheng, Zunqing; Yao, Mingfa (Frontiers in Energy Research, 2022)
Peak combustion pressures (PCP) are increased in heavy-duty diesel engines to obtain higher thermal efficiency. Fuel injection strategy has been a major measure to improve the combustion and emissions of diesel engines. But most existing work of multi-injection strategies was not limited by PCP or was conducted under lower PCP (∼15 MPa). In this study, an experimental study is conducted to further improve the understanding of injection strategies on engine performance under a relative higher peak combustion pressure at 20 MPa. The four tested injection strategies are single main injection, pilot-main injection, main-post injection, and pilot-main-post injection. The effects of PCP on brake thermal efficiency (BTE) and other engine performances are also investigated under the same NOx emissions conditions. Results indicate that more advanced injection timing can obtain higher BTE, while the injection pressure has less effects on BTE as it is higher than 120 MPa. For double-injection, the smaller interval on pilot-main or main-post and the less pilot or post mass improves BTE and emissions. The PCPs are linearly correlated to the BTE, peak average temperature, and peak pressure rise rate (PRR), and the increment of BTE, peak average temperature, and peak PRR are about 0.3%, 30 K, and 0.1 MPa/CA for every 1 MPa increase in PCP, respectively. This also means that the improvement on BTE by the increase of PCP imparts greater thermal and mechanical loads on engine materials and components. At 20 MPa PCP, based on the optimized injection strategies, the BTE of all four strategies is about 42.8%, and the peak PRR of all four strategies is about 0.8 MPa/CA. At a given NOx emission of 17.4 g/kWh and approximate 20 MPa PCP, all four injection strategies have minor effects on distribution of fuel energy and emissions. Therefore, it can be concluded that the injection strategies have fewer effects on BTE and emissions at the higher peak combustion pressure of 20 MPa; the main purpose of injection strategies is to reduce the peak PRR or reach the potentially required temperature for aftertreatment devices.